Analysis HOTS Problem Solving: Student Learning Outcomes from Student Facilitator and Explaining and Geogebra-Assisted Discovery Learning Models - Linda Linda; Abdillah Abdillah; Vera Mandailina; Syaharuddin Syaharuddin (STAI Hubbulwathan Duri, 2024)
Educators need to think about the difficulties that students often face when faced with high-order thinking skills in order to improve the teaching and learning system through the use of the right learning methods. This study aims to compare learning outcomes between using the Student Facilitator and Explaining the learning model with Discovery Learning powered by Geogebra to help students be critical, creative, and innovative in solving problems in the form of High Order Thinking Skills questions to think about in the context of science and everyday life. This experiment uses quantitative methods and is conducted in two classes XI with a total of 32 samples, namely 13 students of Experiment A and 19 students of Experiment B. This study uses instruments in the form of HOTS questions, consisting of 5 descriptive questions with pre-test and post-test designs so that the generated data is tested with JASP and SPSS software. In the Geogebra-powered Discovery Learning model, the p-value is 0.059 with an average of 20.000, while in the Geogebra-powered Student Facilitator and Explaining learning model, the p-value is 0.276 with an average of 52.947. Thus, the learning model suitable for the application of Geogebra software is Student Facilitator and Explaining based on the generated data and has a higher learning outcome value than the pre-test and post-test of the Discovery Learning learning model. This research can be a reference for education in education because of the need for proper technology to support the teaching and learning activities for students.